2022
DOI: 10.1371/journal.pone.0271501
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 patient characteristics in a large electronic health record database in the United States: A cohort study

Abstract: Background Electronic health record (EHR) databases provide an opportunity to facilitate characterization and trends in patients with COVID-19. Methods Patients with COVID-19 were identified based on an ICD-10 diagnosis code for COVID-19 (U07.1) and/or a positive SARS-CoV-2 viral lab result from January 2020 to November 2020. Patients were characterized in terms of demographics, healthcare utilization, clinical comorbidities, therapies, laboratory results, and procedures/care received, including critical car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Additionally, most patients in our study identified as White, regardless of HIV status. Though the differences in age and ethnicity were significant between groups in our study, the findings are most likely due to the distribution of COVID-19 in the U.S., particularly during the early stages of the pandemic [17].…”
Section: Discussioncontrasting
confidence: 57%
“…Additionally, most patients in our study identified as White, regardless of HIV status. Though the differences in age and ethnicity were significant between groups in our study, the findings are most likely due to the distribution of COVID-19 in the U.S., particularly during the early stages of the pandemic [17].…”
Section: Discussioncontrasting
confidence: 57%
“…The reported mortality in our cohort was lower than reported in other European countries, for example France (first wave 16.2%, second wave 17.7%) or Germany (first wave 19.1%, second wave 19.8%) which may results from difference in populations admitted to the hospital and systems of care 29 , 30 . Interestingly, no mortality reduction was observed across the two waves in these latter countries, whereas a large North American database reported an important reduction of critical care admission (30.9% to 13.3%) among hospitalized patients from spring to November 2020, but did not adjust for demographic variables, comorbidities or markers of disease severity 31 . Another cohort including 51 510 COVID patients reported a mortality reduction over time for patients with a positive rtPCR testing, but not in the group of clinically diagnosed COVID-19 infections 32 .…”
Section: Discussionmentioning
confidence: 91%
“…. Interestingly, no mortality reduction was observed across the two waves in these latter countries, whereas a large North American database reported an important reduction of critical care admission (30.9% to 13.3%) among hospitalized patients from spring to November 2020, but did not adjust for demographic variables, comorbidities or markers of disease severity31 . Another cohort including 51 510 COVID patients reported a mortality reduction over time for patients with a positive rtPCR testing, but not in the group of clinically diagnosed COVID-19 infections32 .…”
mentioning
confidence: 89%
“…Over the course of the pandemic, physicians learned how to better manage the disease, thus changes in trends from 2020 to 2021 might indicate emerging subphenotypes or better laboratory monitoring practices [21][22][23] . Information about comorbidities and best practices for monitoring patients is valuable for saving lives and reducing burden on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%